Metal foam supported catalyst and method for producing same

By heat-treating nickel foam and aluminum powder to form an alloy and oxidizing treatment, the problem of low adhesion performance of existing catalysts is solved, and the mechanical stability and durability of the catalyst are significantly improved.

JP7670693B2Active Publication Date: 2025-04-30ALANTUM OJROPE GMBKH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022519026
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-25
Filing Date
2020-09-25
Publication Date
2025-04-30
Estimated Expiration
2040-09-25

AI Technical Summary

Technical Problem

Existing metal foam supports catalysts with low adhesion properties and are prone to fall off when mechanically loaded or streamed through the reactor, resulting in a shorter catalyst life and may affect plant operation.

Method used

By heat-treating the nickel foam and aluminum powder to form an alloy and oxidizing treatment, an aluminum oxide layer is formed to improve the adhesion performance of the nickel foam surface.

Benefits of technology

It significantly improves the adhesion of the catalyst to metal foam, enhances mechanical stability and durability, avoids the problem of catalyst falling off, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for producing a supported catalyst, the method comprising the steps of providing a metal foam A made of metallic nickel, applying an aluminum-containing powder MP to the metal foam A to obtain a metal foam AX, heat-treating the metal foam AX to form an alloy between the metal foam A and the aluminum-containing powder MP to obtain a metal foam B, oxidizing the metal foam B to obtain a metal foam C, and applying a catalytically active layer comprising at least one support oxide and at least one catalytically active component to at least a portion of the surface of the metal foam C to obtain a supported catalyst. The present invention further relates to a supported catalyst obtained by the method and its use in chemical conversions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] background The present invention relates to a method for producing a supported catalyst comprising the steps of coating a nickel foam with aluminum, followed by a heat treatment to form an alloy between the nickel foam and the aluminum, followed by an oxidation treatment of the aluminum surface and applying a catalytically active layer comprising at least one support oxide and at least one catalytically active component. The present invention further relates to a supported catalyst obtained by this method and its use in chemical conversions.

[0002] prior art From the prior art, it is known to use metal foams as supports for catalytically active coatings. Catalytically active coatings on metal supports typically consist of a support oxide, which increases the microscopic surface, and a catalytically active metal applied to the support oxide (see, for example, WO 9511752). The monolithic supported catalysts thus obtained can be used in various applications, but their usability is limited by the very poor adhesion of the catalytically active coating, which consists mainly of oxide components, to the metallic support. Poor adhesion leads to parts of the catalytically active layer peeling off under mechanical load, and possibly even during operation of the supported catalyst in a flow-through reactor, with an associated shortening of the catalyst's lifespan and possibly even disruption of the plant's operation due to the peeled off solid particles.

[0003] Sol-gel methods are also used to coat metal foams as catalyst supports, but these methods require special equipment and the use of expensive reagents that are hazardous and difficult to handle.

[0004] Another method for producing metal foam supported catalysts known from the prior art is based on the ability to form a relatively stable oxide layer on the metal surface by "atomic layer deposition" (ALD). For example, US20120329889 discloses a method for producing metal foam supported catalysts for Fischer-Tropsch synthesis, in which a thin Al2O3 film is formed on the metal foam by atomic layer deposition (ALD), followed by application of an oxide coating by dip coating, drying, and subsequent calcination. US20120329889 explicitly mentions that a stable bond between the metal foam surface and the oxide coating is difficult (see paragraphs

[0068] to

[0069] ), and that this is achieved by application of an intermediate oxide layer by ALD. However, the method disclosed in US20120329889 is very complex in terms of equipment.

[0005] In view of the limited availability of stable metal foam supported catalysts, it was an object of the present invention to provide a method for producing catalytically coated supported catalysts from catalytically inactive metal foams that is as simple as possible and suitable for mass production, whereby it is desirable to avoid clogging of the pores provided by the foam base structure, to allow the catalytic coating to be applied as easily as possible, and to be characterized by very good adhesion to the metal foam. The method of the present invention and the products obtained thereby meet this requirement.

[0006] The present invention The method for producing a supported catalyst according to the present invention comprises the steps of: (a) providing a metal foam A made of metallic nickel; (b) applying an aluminum-containing powder MP to the metal foam A to obtain a metal foam AX; (c) heat treating the metal foam AX to form an alloy between the metal foam A and the aluminum-containing powder MP to obtain a metal foam B, Here, the maximum temperature of the heat treatment of the metal foam AX is in the range of 680 to 715°C, and The total time of the heat treatment in the temperature range of 680 to 715°C is 5 to 240 seconds; (d) oxidizing the metal foam B to obtain a metal foam C; (e) applying a catalytically active layer comprising at least one support oxide and at least one catalytically active component to at least a portion of the surface of the metal foam body C to obtain a supported catalyst; Includes.

[0007] From the prior art, nickel foams are known as an alternative to classical Raney-type catalysts, which are first alloyed with aluminum and then partially leached again (see, for example, EP 2 764 916 A1). The foams thus obtained are activated all-metallic Raney-type catalysts, which are typically used for hydrogenation reactions.

[0008] Furthermore, the prior art also knows metal foams which are first alloyed with aluminum and then oxidized (see Wen-Wen Zeng et al. “Synthesis and compression property of oxidation-resistant Ni-Al foams”, Acta metallurgica Sinica, Band 30, Nr. 10, 1. October 2017, pp. 965-972). However, in the method of Wen-Wen Zeng et al., the entire cross section of the original metal foam is alloyed with aluminum (see “Conclusions” on page 972), whereas in the method according to the invention the alloy formation is limited to the upper layer of the metal foam, so that non-alloyed areas remain in the central region of the metal foam.

[0009] The experimental results obtained with the present invention show that the choice of temperature conditions for the heat treatment for alloy formation has a considerable influence on the results. In the method according to the invention, the alloy formation can be limited to the upper layer of the metal foam, leaving a non-alloyed area in the central region of the metal foam. The presence of this non-alloyed area affects in particular the mechanical stability of the resulting supported catalyst. The fracture / compression strength decreases significantly with increasing degree of alloying, and complete alloying of the metal foam leads to a very brittle supported catalyst that is prone to fracture under mechanical stress. Continuously operated fixed bed reactors for large industrial applications have a fixed bed volume of 100 m 3 This situation has great practical implications, since the loads can reach several tonnes and, depending on the bulk density and height of the fixed bed used, can amount to several metric tons below. If the supported catalyst used to construct the fixed bed does not have sufficient mechanical stability and load-bearing capacity to support these weights over several thousand hours of operation, the support structure can break and, as a result, the catalytically active areas can be mechanically destroyed (catalyst breakage). The broken material can be discharged together with the fluid from the reactor into adjacent parts of the plant and / or cause caking in the fixed bed. In either case, this can cause major disruptions to the plant's operation.

[0010] In the context of the present invention, metal foam A is understood to mean a foamed metal body. Foamed metal bodies are disclosed, for example, in Ullmann's Encyclopedia of Industrial Chemistry, chapter "Metallic Foams", published online on 15 July 2012, DOI: 10.1002 / 14356007.c16_c01.pub2. In principle, metal foams with different morphological properties in terms of pore size and pore shape, layer thickness, areal density, geometric surface, porosity, etc. are suitable. Preferably, the metal foam A has a density of 400 to 1500 g / m 2, a pore size of 400 to 3000 μm, preferably 400 to 800 μm, and a thickness of 0.5 to 10 mm, preferably 1.0 to 5.0 mm. Its production can be carried out by known methods. For example, an organic polymer foam can first be coated with nickel and then the polymer can be removed by pyrolysis, whereby a nickel foam is obtained. For the coating with nickel, the organic polymer foam can be brought into contact with a solution or suspension containing nickel. This can be carried out, for example, by spraying or immersion. Deposition by chemical vapor deposition (CVD) is also possible. Polymer foams suitable for producing moulded bodies in the form of foams preferably have a pore size in the range of 100 to 5000 μm, particularly preferably 450 to 4000 μm, in particular 450 to 3000 μm. Suitable polymer foams preferably have a layer thickness of 0.5 to 10 mm, particularly preferably 1.0 to 5.0 mm. Suitable polymer foams preferably have a layer thickness of 300 to 1200 kg / m 3 The specific surface area is preferably 100 to 20,000 m 2 / m 3 , particularly preferably 1000 to 6000 m 2 / m 3 The porosity is preferably in the range of 0.50 to 0.95.

[0011] The metal foam A used in step (a) of the method according to the invention can have any shape, for example cubic, rectangular, cylindrical, etc. However, the metal foam can also be shaped, for example as a monolith.

[0012] The application of the aluminium-containing powder MP in step (b) of the method according to the invention can be carried out in various ways, for example by bringing the metal foam A into contact with the composition of aluminium-containing powder MP by rolling or immersion, or by applying the composition of aluminium-containing powder MP by spraying, scattering or casting. For this purpose, the composition of aluminium-containing powder MP can be present either as a suspension or in the form of a powder.

[0013] Here, preferably, before the actual application of the composition of the aluminum-containing powder MP to the metal foam A in step (b) of the method according to the invention, the metal foam A is previously impregnated with a binder. This impregnation can be carried out, for example, but not limited to, by spraying the binder or by immersing the metal foam A in the binder. The composition of the metal-containing powder MP can then be applied to the metal foam A thus prepared.

[0014] Alternatively, the composition of the binder and the aluminium-containing powder MP can be applied in one step: for this, the composition of the aluminium-containing powder MP is suspended in the liquid binder itself before application, or the composition of the aluminium-containing powder MP and the binder are suspended in the auxiliary liquid F.

[0015] The binder is a composition that can be completely converted into a gaseous substance by heat treatment in the temperature range of 100 to 400 ° C. and contains an organic compound that promotes adhesion of the aluminum-containing powder MP composition to the metal foam. Preferably, the organic compound is selected from the following group: polyethyleneimine (PEI), polyvinylpyrrolidone (PVP), ethylene glycol, mixtures of these compounds. PEI is particularly preferred. The molecular weight of polyethyleneimine is preferably in the range of 10,000 to 1,300,000 g / mol. The molecular weight of polyethyleneimine (PEI) is preferably in the range of 700,000 to 800,000 g / mol.

[0016] The auxiliary liquid F must be suitable for suspending the aluminum-containing powder MP composition and the binder and must be capable of being completely converted into a gaseous substance by heat treatment in the temperature range of 100-400° C. Preferably, the auxiliary liquid F is selected from the following group: water, ethylene glycol, PVP, and mixtures of these compounds. Usually, when an auxiliary liquid is used, the binder is suspended in water at a concentration in the range of 1-10% by weight, and then the aluminum-containing powder MP composition is suspended in this suspension.

[0017] The aluminum-containing powder MP used in step (b) of the method according to the invention contains powdered aluminum and may further contain additives that contribute to improving the flowability and water resistance. Such additives must be completely convertible into gaseous substances by heat treatment in the temperature range of 100 to 400°C.

[0018] The aluminum-containing powder MP preferably has an aluminum content in the range of 80-99.8% by weight. Preference is given here to powders in which the aluminum particles have a particle size of 5 μm to 200 μm. Particular preference is given to powders in which 95% of the aluminum particles have a particle size of 5 μm to 75 μm. The aluminum-containing powder MP may contain, in addition to the aluminum component in simple form, an aluminum component in oxidized form. The oxidized component is usually in the form of an oxidizing compound, such as, for example, an oxide, hydroxide and / or carbonate. Typically, the weight fraction of aluminum oxide is in the range of 0.05-10% by weight of the total weight of the aluminum-containing powder MP.

[0019] In step (c) of the method according to the invention, one or more alloys are formed by heat treatment. Experimental results obtained in accordance with the invention have shown that the choice of temperature conditions for the heat treatment for alloy formation has a significant influence on the course of the alloy formation. In the method according to the invention, the alloy formation can be limited to the upper layer of the metal foam, leaving a non-alloyed region in the central region of the metal foam.

[0020] In step (c) of the method according to the invention, the metal foam AX is heat treated to form an alloy between the metal foam A and the aluminum-containing powder MP to obtain a metal foam B, wherein the maximum temperature of the heat treatment of the metal foam AX is in the range of 680-715°C and the total time of the heat treatment in the temperature range of 680-715°C is 5-240 seconds.

[0021] The heat treatment usually involves a stepwise heating of the metal foam AX followed by cooling to room temperature. The heat treatment is carried out under inert gas or reducing conditions. Reducing conditions means the presence of a gas mixture comprising hydrogen and at least one gas that is inert under reaction conditions. For example, a gas mixture comprising 50% by volume of N2 and 50% by volume of H2 is suitable. Nitrogen is preferably used as the inert gas. The heating can be carried out, for example, in a belt furnace. Suitable heating rates are in the range of 10-200 K / min, preferably 20-180 K / min. During the heat treatment, the temperature is usually first increased from room temperature to about 300-400 °C, at which temperature moisture and organic components are removed from the coating for a time of about 2-30 minutes. The temperature is then increased to the range of 680-715 °C, which leads to alloy formation between the metal foam A and the aluminum-containing powder MP. The metal foam is then quenched by contacting it with an inert gas environment at a temperature of about 200 °C.

[0022] In order to limit the alloy formation to the upper region of the metal foam and leave a non-alloyed region inside the metal foam, in the metals involved in the present invention, it is necessary that the maximum temperature of the heat treatment of the metal foam AX in step (c) is in the range of 680-715 ° C and, moreover, that the total time of the heat treatment in the temperature range of 680-715 ° C is 5-240 seconds. To a certain extent, the duration of the heat treatment may compensate for the level of the maximum treatment temperature and vice versa. However, it has been found that the frequency of experiments in which alloys are formed in the upper region of the metal foam and at the same time non-alloyed regions remain inside the metal foam is significantly reduced when the maximum temperature of the heat treatment deviates from the temperature range of 680-715 ° C and / or the duration of the heat treatment in the temperature range of 680-715 ° C is outside the range of 5-240 seconds. If the maximum temperature is too high and / or the time the metal foam remains in the range of the maximum temperature is too long, the alloying proceeds to the deepest layer of the metal foam and no non-alloyed region remains. If the maximum temperature is too low and / or the metal foam remains in the maximum temperature range for too short a time, alloy formation may never begin.

[0023] The heat treatment of the metal foam in step (c) of the method according to the invention results in the formation of an aluminum-containing phase. The weight ratio V of metal foam B to metal foam A is V=m(metal foam B) / m(metal foam A), which is an indication of how much aluminum has been alloyed into the foam in step (c) of the method according to the invention. In a preferred embodiment, the weight ratio V of metal foam B to metal foam A is in the range of 1.1:1 to 1.5:1. In a further preferred embodiment, the weight ratio V of metal foam B to metal foam A is in the range of 1.2:1 to 1.4:1.

[0024] In step (d) of the method according to the invention, the metal foam B is subjected to an oxidation treatment to obtain the metal foam C.

[0025] The purpose of the oxidation treatment of the metal foam B in step (d) of the method according to the invention is to provide an external aluminum oxide layer on the aluminum present at the surface of the metal foam B. This can be achieved, for example, by exposing the metal foam B to an oxidizing gas atmosphere (e.g. air) under heating or by first forming aluminum hydroxide on the surface of the metal foam B, for example by contact with an alkaline solution, and then converting this aluminum hydroxide into aluminum oxide by heat treatment under oxidizing conditions.

[0026] In order to expose the metal foam B to an oxidizing gas atmosphere in a heated state, for example, it is sufficient to heat the metal foam to an appropriate temperature in a furnace while introducing air.

[0027] When the metal foam B is heated under air introduction without forming aluminum hydroxide in advance, the temperature is preferably selected from 200° C. to 1200° C., or 200° C. to 1000° C., or 200° C. to 750° C. Preferably, according to the present invention, the thermal oxidation is carried out in air at a temperature of 200° C. to 680° C. for a time of 1 to 60 minutes.

[0028] If aluminum hydroxide is first formed on the surface of the metal foam B, for example by contact with an alkaline solution, and then heat treatment is carried out, at least a portion of the aluminum present on the surface is first converted into aluminum hydroxide, and then at least a portion of this aluminum hydroxide formed on the surface is converted into aluminum oxide.

[0029] Preferably, conversion of at least a portion of the aluminum present at the surface to aluminum hydroxide is accomplished by contacting the metal foam with an aqueous alkaline solution.

[0030] Particularly preferably, the alkaline aqueous solution contains sodium hydroxide, potassium hydroxide, lithium hydroxide, or a combination thereof in a concentration of 0.05 to 30% by weight, preferably 0.5 to 5% by weight, and the metal foam B is contacted with the alkaline aqueous solution for a period of 5 to 120 minutes, preferably up to 30 minutes, particularly preferably up to 10 minutes. This treatment can be carried out in a temperature range of 10°C to 110°C. Treatment at 20°C (room temperature) is preferred.

[0031] Thereafter, at least a part of the aluminum hydroxide formed on the surface is thermally converted to aluminum oxide in an oxidizing atmosphere by heating to a temperature of 20°C (room temperature) to 700°C for a period of 1 minute to 8 hours under the introduction of air. Preferably, according to the present invention, the thermal oxidation is carried out in air at a temperature of 200°C to 680°C for a period of 1 to 60 minutes.

[0032] Metal foam C serves as a support for a suitable catalyst, which may be specifically selected for the particular reaction to be catalyzed.

[0033] In step (e) of the method according to the invention, at least a part of the surface of the metal foam body C is provided with a catalytically active layer comprising at least one support oxide and at least one catalytically active component to obtain a supported catalyst.

[0034] The metal foam C according to the invention can be particularly well applied with the catalytically active layer according to the invention, since the aluminum oxide coating produced on the surface of the metal foam C ensures particularly good bonding of the support oxide, resulting in a long durability and service life as well as a particularly high mechanical stability, in particular wear stability.

[0035] The catalytically active layer comprising at least one support oxide and at least one catalytically active component can be applied to the metal foam C, for example by suction or drawing of the coating suspension through the open cavities of the open-celled metal foam C, since in terms of the open cavities and high form stability the metal foam C is similar to the monolithic substrates used in automotive exhaust catalysts. It is also possible to apply the coating suspension by immersion (so-called "dip coating") or spraying (so-called "spray coating"). Which of the application methods basically known in the prior art is preferred depends firstly on the composition and flow properties of the coating suspension and secondly on the actual structure of the metal foam according to the invention. Dip coating is suitable for the coating of all metal foams according to the invention, since it has the highest possible tolerance to the various properties of the coating suspension.

[0036] According to the present invention, in step (e), the contact with the coating suspension is followed by calcination of the coated metal foam to obtain the supported catalyst.

[0037] According to the invention, the catalytically active layer comprises at least one carrier oxide. A carrier oxide in the sense of the invention is typically a layer having a thickness of 50 to 200 μm. 2 / g. These support oxides have several functions in the finished catalyst. Firstly, they serve to increase at the microscopic level the macroscopic, i.e. geometrical, surface provided by the metal foam according to the invention, which in the context of the present invention is called the contact surface between the catalyst and the reaction medium. Secondly, they can interact with the catalytically active species and influence the course of the reaction. For example, the choice of the support oxide influences the selectivity of complex hydrogenation reactions in which several functional groups of the organic substrate molecules can react with hydrogen. Furthermore, the support oxides provide a fine surface on which the catalytically active components are distributed. Furthermore, the support oxides form a matrix in which further functional components or additives can be dispersed, which serves to adjust the specific catalytic functions when adapting the catalyst to a specific application.

[0038] Preferably, the support oxide is selected from the group consisting of aluminum oxide, silicon dioxide, titanium oxide, and mixtures thereof.

[0039] As the catalytically active component of the catalytically active layer, a transition metal or a transition metal compound is used, and the transition metal is preferably selected from the group consisting of iron, ruthenium, osmium, cobalt, rhodium, iridium, nickel, palladium, platinum, cerium, copper, silver, gold, and mixtures thereof.

[0040] As further functional components and additives, the catalytically active layer can comprise inorganic oxides, preferably selected from oxides of alkaline earth metals, oxides of transition metals, oxides of rare earths, oxides of aluminum and gallium, oxides of silicon, germanium and tin, and / or mixtures thereof.

[0041] The catalytically active layer according to the invention may comprise one or more support oxides, one or more catalytically active components and, optionally, further functional components and additives.

[0042] To apply the catalyst to the metal foam according to the invention, a coating suspension is produced by introducing the components into water. Here, the catalyst components are applied to the support oxide, which is either previously impregnated with a corresponding metal salt solution (precursor solution) or by adding the precursor solution directly to the coating suspension and, if appropriate, by precipitating or chemically induced deposition or decomposition of the precursor compound on one or more support oxides already in suspension. Functional components and additives can also be introduced in this way or added directly as oxidizing solids. Alternatively, all components of the catalyst arising from soluble precursors can be added by impregnation after application of the support oxide to the metal foam according to the invention. The choice of production method depends on the target composition of the resulting catalyst and the properties to be adjusted.

[0043] Preferably, the immobilization of the catalytically active layer applied to the metal foam in step (e) of the method according to the invention is carried out by calcination in air.

[0044] According to the invention, the calcination is carried out in air at a temperature between 200°C and 800°C for a time between 1 minute and 8 hours. Preferably, according to the invention, the calcination is carried out in air at a temperature between 200°C and 680°C for a time between 1 minute and 480 minutes. Particularly preferably, the calcination is carried out in air at a temperature between 300°C and 650°C for a time between 1 minute and 480 minutes.

[0045] Preferably, according to the present invention, the thermal oxidation in step (d) is carried out in air at a temperature between 200° C. and 680° C. for a time between 1 and 60 minutes, and the calcination in step (e) is carried out in air at a temperature between 200° C. and 680° C. for a time between 1 and 480 minutes.

[0046] The method for producing the supported catalyst according to the present invention is significantly less expensive than existing methods. Moreover, metal foams consisting only of the metallic components nickel and aluminum form a pure aluminum oxide layer on the surface due to the excess of Al, which acts as a diffusion barrier between the support material and the catalyst layer.

[0047] Catalyst layers based on the support oxide aluminum oxide and aluminum oxide on the surface of metal foams are similar systems, which means they have similar expansion coefficients, low flaking during thermal loading, and excellent compound stability after the calcination process.

[0048] In addition to the process for preparing the supported catalyst according to the invention, the supported catalyst itself obtainable by said process and its use in chemical conversions are also provided by the invention.

[0049] The supported catalyst according to the invention can be advantageously used, for example, in fixed bed chemical processes.

[0050] Working Example 1.Providing metal foam Six metallic foam bodies (a–f) made of nickel were prepared by electrochemically depositing nickel onto polyurethane foam and then pyrolyzing the plastic part (manufacturer: AATM, dimensions: 100 mm × 100 mm × 2 mm, weight per unit area: 1000 g / m). 2 , average pore size: 580 μm).

[0051] 2. Aluminum supplementation After that, the metal foams a, b, c, d, and e were first sprayed with a binder solution (aqueous solution of polyethyleneimine (2.5 wt%)), and then powdered aluminum (manufacturer: AMG, average particle size: <63 μm, 3 wt% ethylenebis(stearamide) added) was applied as a dry powder (approximately 400 g / m 2 ).

[0052] 3.Heat treatment The metal foams a, b, c, d, and e were then subjected to heat treatment in a furnace under a nitrogen atmosphere by first heating them from room temperature to the maximum temperature in about 15 minutes, holding them at this temperature for a specified time, and then quenching them by contacting them with a nitrogen atmosphere at 200°C.

[0053] Maximum temperature of metal foams a, d, e: 700℃ for 2 minutes Temperature change of metal foam b: 600℃ for 2 minutes Temperature change of metal foam c: 750°C for 2 minutes.

[0054] 4. Determination of the degree of alloying The extent of alloy formation in the metal foams was then measured. To this end, cross sections of the metal foams were examined using a microscope and a scanning electron microscope. In metal foams a, d, and e, alloy formation occurred on the surface but non-alloyed regions remained inside the foam, whereas no alloy formation occurred in metal foam b, and in metal foam c, alloy formation had progressed to the extent that no non-alloyed regions remained inside the foam.

[0055] 5. Oxidation treatment Next, the metal foam bodies a and d were subjected to an oxidation treatment.

[0056] The metal foam a was exposed to an oxidizing gas atmosphere in a heated state by heating the metal foam to 700° C. in a furnace under the introduction of air.

[0057] Metal foam d was first contacted with an alkaline solution (5 wt % NaOH aqueous solution) for 10 minutes at 20° C. Then, metal foam d was dried in air.

[0058] 6.Comparison Processing The previously untreated metal foam f was provided with an aluminium oxide layer as described in the prior art (see WO 95 / 11752, Example 3) For this purpose, the metal foam f was completely immersed in a saturated sodium aluminate solution for 3 hours, then shaken in deionised water until the hydrolysis reaction had subsided and finally heated at 500° C. for 3 hours under air introduction.

[0059] 7. Application of catalytically active layer Metal foams a, d, e and f were then provided with a catalytically active layer by spraying. For this purpose, the metal foam was moistened with water. A 2.5% polyethyleneimine suspension was then stirred with high surface area χ-aluminum oxide. The water / polyethyleneimine and aluminum oxide mixture was sprayed. This spraying was followed by a drying step at 140° C. in air in a drying oven for 30 min. For calcination, the samples were fired in a furnace at 650° C. for 5 h. The steps of coating, drying and calcination were repeated several times until the desired coating amount was applied.

[0060] 8. Testing of the Supported Catalyst Finally, the resulting supported catalysts were tested, especially for their durability against mechanical stress, especially for the catalytically active layer on the metal foam. Often a scratch test can be carried out to check the bonding quality of the oxide catalytically active layer to the support foam. However, this test is not possible in the present case due to the irregular structure of the foam. Therefore, to check the mechanical stability of the catalytically active layer, a temperature change test was carried out, which is an indicator of the bonding quality of the oxide layer to the support foam. For this purpose, metal foams a, d, e and f were heated to 500 °C and then quenched in cold water. The amount of loss for each sample, i.e. the weight of the peeled off catalytic layer, was then determined by filtering, drying and weighing the peeled off material.

[0061] The following results were obtained: Metal foams a and d: loss of 3 mg Metal foam f: 10 mg loss Metal foam e: 50 mg loss

[0062] The catalytically active layers on metal foams a and d showed high durability against mechanical stress, whereas the durability of the catalytically active layer on metal foam f was significantly lower, and the durability of the catalytically active layer on metal foam e was very low.

Claims

1. A method for producing a supported catalyst, comprising the steps of: (a) providing a metal foam A made of metallic nickel; (b) applying an aluminum-containing powder MP to the metal foam body A to obtain a metal foam body AX; (c) heat-treating the metal foam AX to form an alloy between the metal foam A and the aluminum-containing powder MP to obtain a metal foam B, Here, the maximum temperature of the heat treatment of the metal foam body AX is in the range of 680 to 715 ° C., and a total time for the heat treatment in the temperature range of 680 to 715° C. is 5 to 240 seconds; (d) oxidizing the foamed metal B to obtain a foamed metal C; (e) applying a catalytically active layer comprising at least one support oxide and at least one catalytically active component to at least a portion of the surface of the metal foam body C to obtain a supported catalyst; A method comprising:

2. The oxidation treatment of the metal foam body B in the step (d) is as follows: heating the metal foam B in contact with an oxidizing gas atmosphere without the prior formation of aluminum hydroxide on the surface of said metal foam; - heating the foamed metal body B in contact with an oxidizing gas atmosphere after previously forming aluminum hydroxide on the surface of the foamed metal body; The method of claim 1 , wherein the compound is selected from the group consisting of:

3. 3. The method according to claim 1 or 2, wherein for the oxidation treatment of the metal foam B in step (d), the metal foam B is heated in contact with an oxidizing gas atmosphere without prior formation of aluminum hydroxide on the surface of the metal foam.

4. 4. The method of claim 3, wherein said heating in contact with an oxidizing gas atmosphere is carried out in air at a temperature between 200° C. and 680° C. for a time period between 1 and 60 minutes.

5. 3. The method according to claim 1 or 2, wherein for the oxidation treatment of the metal foam B in step (d), aluminum hydroxide is formed on the surface of the metal foam beforehand, and then the metal foam B is contacted with an oxidizing gas atmosphere and heated.

6. The method of claim 5 , wherein aluminum hydroxide is formed on the surface by contacting the metal foam with an aqueous alkaline solution.

7. 7. The method of claim 6, wherein the alkaline aqueous solution comprises sodium hydroxide, potassium hydroxide, lithium hydroxide, or a combination thereof, and the metal foam is contacted with the alkaline aqueous solution for a time period of up to 30 minutes.

8. 8. The method according to claim 5, wherein the heating of the aluminum hydroxide preformed on the surface of the metal foam body in contact with an oxidizing gas atmosphere is carried out in air at a temperature between 200° C. and 680° C. for a time period between 1 and 60 minutes.

9. 9. The method according to claim 1, wherein the support oxide of the catalytically active layer applied in step (e) is selected from the group consisting of aluminum oxide, silicon dioxide, titanium oxide and mixtures thereof.

10. 10. The process of claim 1, wherein the catalytically active component is a transition metal or a transition metal compound, the transition metal being selected from the group consisting of iron, ruthenium, osmium, cobalt, rhodium, iridium, nickel, palladium, platinum, cerium, copper, silver, gold, and mixtures thereof.

Citation Information

Patent Citations

  • Surface modified metal foam, method of making same, and use thereof

    JP2016513173A

  • Method of coating catalyst carrier layer of metal-metal oxide, method of depositing active catalyst particles onto metal substrates for preparing metal monolith catalyst modules, and module thereby

    US20040086637A1